TEACHING BASIC VOCABULARY AND PHRASES - Anorboyeva Mahbuba; Ahmadjonova Gulhayo (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Vocabulary  is  understanding how  to  use  words  in  relation  to  their meaning. Developing new vocabulary involves more than just looking up words in a dictionary and using those words in sentences. Students' vocabulary grows throughout their lifetime through direct and indirect learning.